The story of Hollywood an illustrated history - Williams, Gregory Paul (BL Press, 2011)
The Story of Hollywood follows Hollywood from its dusty origins to its glorious rise to stardom. Lavishly illustrated with over 800 vintage images from the author's private collection, the book tells the complete story of Hollywood including its eventual decline and urban renewal. The Story of Hollywood brings new insights to readers with a passion for Hollywood and its place in the history of film, radio, and television
Keywords: Motion pictures / California / Hollywood (Los Angeles) / History; Motion picture industry / California / Hollywood (Los Angeles) / History; Hollywood (Los Angeles, Calif.) / History / Pictorial works; Motion picture industry; Motion pictures; California / Los Angeles / Hollywood / https://id.oclc.org/worldcat/entity/E39PBJpYCXdfWCCGDF38RTMgKd; Film industry / Hollywood (Los Angeles) / History; illustrated books; Illustrated works; History; Pictorial works; Ouvrages illustrés